Novel Pyrazoline‐based Organometallic Compounds Containing Ferrocenyl and Quinoline units: Synthesis, Characterization and Microbial susceptibilities. (16th January 2018) - Parveen, Humaira; Alatawi, Raedah Aiyed Suliman; Alsharif, Meshari A.; Alahmdi, Mohammed Issa; Mukhtar, Sayeed; Khan, Salman Ahmad; Hasan, Sadaf; Khan, Asad U.
Abstract : Some novel pyrazoline‐based organometallic compounds were synthesized as new leads in antimicrobial chemotherapy. The structures of compounds were elucidated by different spectroscopic techniques and elemental analyses. All compounds were investigated for in vitro antimicrobial studies against fifteen ATTC bacterial and fungal strains. The microbial susceptibility of these compounds revealed that all the tested compounds gave good minimum inhibitory concentration (MIC) values against the tested organisms that are either similar or even better than the reference drugs amoxicillin and fluconazole, which gave MIC values 8‐64 μg/ml against bacterial and 64 μg/ml against fungal strains, respectively. Among all compounds, compound (4d ) 1‐(5‐(4‐chlorophenyl)‐3‐ferrocenyl‐4, 5‐dihydropyrazol‐1‐yl)‐2‐quinolin‐8‐yloxy) ethanone, emerged out the most promising antimicrobial organometallic derivative with MIC values against all the strains ranging from 8‐32 μg/ml. Other compounds gave a range of MIC values between 16‐64 μg/ml against S. bovis, 16‐32 μg/ml against E. coli, and C. tropicalis except compound (4d) which gave MIC 8 μg/ml against S. bovis and E. coli, whereas 32 μg/ml against C. tropicalis . Collectively, these compounds gave a lower MIC value between 32‐64 μg/ml against both of the biofilm forming strains namely, P. aeruginosa and S. mutans . The results of microbial susceptibility concluded that these novel organometallic compounds are new leads in antimicrobial chemotherapy and can be very useful for further optimization work on microbial chemotherapy. Abstract : Novel pyrazoline‐based organometallic compounds containing ferrocenyl and quinoline units were synthesized, well characterized and screened for microbial susceptibility. The results revealed that these compounds are new leads in antimicrobial chemotherapy as all the tested compounds gave an extraordinary minimum inhibitory concentration (MIC) than the reference drugs Amoxicillin and Fluconazole. Among all, compound (4d) was emerged as the most promising antimicrobial organometallic derivative.